2017
DOI: 10.1080/19490976.2017.1371894
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction promotes rapid expansion and long-lasting increase of Lactobacillus in the rat fecal microbiota

Abstract: Previous studies indicated that caloric restricted diet enables to lower significantly the risk of cardiovascular and metabolic diseases. In experimental animal models, life-long lasting caloric restriction (CR) was demonstrated to induce changes of the intestinal microbiota composition, regardless of fat content and/or exercise. To explore the potential impact of short and long-term CR treatment on the gut microbiota, we conducted an analysis of fecal microbiota composition in young and adult Fisher 344 rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 35 publications
2
50
0
Order By: Relevance
“…The human gut microbiota is a complex community and is important for the health status of the host . Alterations in the gut microbiota and diet have been found to be associated with the pathogenesis of several human diseases . Probiotic supplementation has been found to be associated with improvements in health and the intestinal microbial composition, and the supplementation of L. fermentum has been shown to modulate the intestinal microbiota in piglets .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human gut microbiota is a complex community and is important for the health status of the host . Alterations in the gut microbiota and diet have been found to be associated with the pathogenesis of several human diseases . Probiotic supplementation has been found to be associated with improvements in health and the intestinal microbial composition, and the supplementation of L. fermentum has been shown to modulate the intestinal microbiota in piglets .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Alterations in the gut microbiota and diet have been found to be associated with the pathogenesis of several human diseases. [36][37][38][39][40] Probiotic supplementation has been found to be associated with improvements in health and the intestinal microbial composition, 24,41 and the supplementation of L. fermentum has been shown to modulate the intestinal microbiota in piglets. 42 As the global composition and the presence of pathogens or beneficial bacteria are relevant to the host's health, we analyzed the composition of the test animals over 13 weeks of feeding of bacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of gut microbiota is shaped mainly by diet [20]. Substantial evidence of dramatic diet-induced changes in microbiota composition resulting from fasting, use of laxatives, and low fat dietary intervention has been obtained; these changes counteract metabolic damages associated with obesity and high-fat diet [21]. Thus, these CR-induced alterations of the intestinal microbiota suggested that animals can establish a balanced gut microbiota composition via CR, providing health advantages to the host.…”
Section: Introductionmentioning
confidence: 99%
“…26 LIP-1 colonized the colon and promoted the growth of beneficial bacteria; the increased SCFAs produced by carbohydrates fermented by the bacteria can reduce intestinal permeability and prevent potentially harmful by-products translocating into the bloodstream and reaching the liver, 41 and they can effectively reduce tissue inflammation and relieve liver damage. 48,49 Furthermore, in physiological conditions, SCFAs are circulated by the blood and delivered to the liver, and increases in SCFAs can inhibit the synthesis of liver CHO and fatty acid. Previous studies have shown that LIP-1 has a good ability to clear intestinal CHO; the ability of certain LIP-1s to survive and grow in the colon is important in decreasing the absorption of dietary CHO from the digestive system to the blood and has the potential to aid in the control of serum and liver CHO.…”
Section: Discussionmentioning
confidence: 99%